Differences in Highly Pathogenic H5N6 Avian Influenza Viral Pathogenicity and Inflammatory Response in Chickens and Ducks - Wang, Bo; Su, Qianqian; Luo, Jing; Li, Meng; Wu, Qiaoxing; Chang, Han; Du, Juan; Huang, Chengmei; Ma, Jiajun; Han, Shuyi; Yuan, Guohui; He, Yapeng; et al. (Frontiers in Microbiology, 2021)
Infection with H5N6 highly pathogenic avian influenza virus caused high mortality in chickens, while ducks often appear to be asymptomatic. But, some recent H5Nx subtype viruses could cause high mortality in ducks. The variation between different species and the mechanisms by which some H5Nx viruses cause death in ducks requires investigation to identify key processes in influenza susceptibility and pathogenesis. Here we characterized two representative H5N6 viruses, A/Pavo Cristatus/Jiangxi/JA1/2016 (JA1) and A/Anas crecca/shanghai/SH1/2016 (SH1), and compared their pathogenicity and expression profiles of immune-related genes in chickens and ducks to identify the elements of the host immune-related response that were involved in disease lethality. Results suggested that H5N6 HPAIVs had higher pathogenic and inflammatory effect in chickens than in ducks. Importantly, the TNF-α, IL-6, IFN-γ and iNOS levels were significantly higher in the lung of SH1 infected chickens compared to those of ducks. And we found higher systemic levels of IL-6 induced by JA1 in chickens than in ducks. In addition, our experiments demonstrated that JA1 was associated with greater pathogenicity in ducks, were accompanied by the excessive expression of iNOS in the brain. These results are helpful to understand the relationship between the pathogenicity of H5N6 AIVs and inflammatory responses to them in chickens and ducks.